2019
DOI: 10.1097/bpb.0000000000000582
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of Gartland type III supracondylar humerus fractures in older children: a retrospective study

Abstract: The aim of this study was to analyse the management of Gartland type III supracondylar humerus fractures in children older than 10 years at our paediatric orthopaedics and to determine the clinical and radiographic long-term effects following open reduction by the small medial approach and cross-fixation with three kirschner wires. Eighty-three cases of Gartland type III supracondylar humerus fractures in children older than 10 years were treated by open reduction by the small medial approach and cross-fixatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
3
24
0
1
Order By: Relevance
“…The results of the present study were found to be compatible with the literature, for both groups. [16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present study were found to be compatible with the literature, for both groups. [16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…(Table 5). 15 In a study done by Gowda et al, all 50 patients who were treated by open reduction and internal fixation with K-wire had reported 10% of ulnar nerve palsy and 83.3% had excellent/good outcome. 16 In a study done by Mazda et al, 92% of children who had undergone open reduction with internal fixation had excellent outcome according to Flynn criteria.…”
Section: Discussionmentioning
confidence: 97%
“…Discussions regarding the potential risk of ulnar nerve injury in case of medial pinning and the insufficiency of lateral pinning alone in providing stability compared to cross pinning are still ongoing [20,21]. Li et al performed a medial incision and inserted one K-wire from the medial aspect and two K-wires from the lateral aspect, and they did not report any complications such as ulnar nerve injury, compartment syndrome, or varus deformity during the follow-up of 83 patients >10 years, and they obtained satisfactory functional and cosmetic outcomes [22]. Lateral pinning was reportedly performed in 48 patients and cross pinning in 39 patients following closed reduction, and cross pinning reportedly provided a more rigid fixation [23].…”
Section: Discussionmentioning
confidence: 99%